2012
DOI: 10.1039/c2ob26028j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of push–pull chromophores by the sequential [2 + 2] cycloaddition of 1-azulenylbutadiynes with tetracyanoethylene and tetrathiafulvalene

Abstract: The azulene-substituted butadiynes have been prepared by Cu-mediated cross-and homo-coupling reaction. The azulene-substituted butadiynes reacted with tetracyanoethylene in a formal [2 + 2] cycloaddition reaction to afford the corresponding 1,1,4,4-tetracyanobutadiene chromophores, respectively, in excellent yields. Further [2 + 2] cycloaddition with TTF and TCNE gave novel donor-10 acceptor chromophores and novel azulene-substituted 6,6-dicyanofulvene derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Notably, there was no further cycloaddition involving the allylic double bond and the TCBD group. One could anticipate that a Diels–Alder reaction would be possible, as observed in other similar compounds . This system is probably too strained to allow for any further reactions, at least at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, there was no further cycloaddition involving the allylic double bond and the TCBD group. One could anticipate that a Diels–Alder reaction would be possible, as observed in other similar compounds . This system is probably too strained to allow for any further reactions, at least at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…[71a] Moreover,the concept of sequential TCNE/ TTF additions was applied to end-capped polyynes. [73] Te trayne 86 a was subjected to stepwise,alternate reactions with TCNE and TTF.T he target [AB]-type oligomer 87 a could eventually be obtained after isolation and characterization of each intermediate.I tw as gratifying to find that one-pot, multicomponent cascade reactions of 86 a with TCNE and TTF also gave 87 a in 21 %y ield (corresponding to 68 %i n each CA-RE process). If the phenyl terminus bears a para-CN group (in 86 b)for better electronic reaction control, the yield of 87 b in the one-pot reaction was even raised to 58 %.…”
Section: Complex Chromophoric Systemsmentioning
confidence: 99%
“…Unfortunately,t hese studies revealed that the expansion of the conjugated system through the 1,3,5-tri(1-azulenyl)benzene core was not effective andt he electronic communication between the 1-AzTCBD units in the molecule was quite small. [41] Similar to the reactiono f1 -ethynylazulenes, 1-azulenylbutadiynesw ere prepared from 1-ethynylazulene derivatives using Glaser-Hayc oupling by reactingt hem with TCNE under mild conditions to give the corresponding 1-AzTCBDs 11 and 12 bearinga ryl alkyne substituents. [39] Recently,K ivala et al reportedt he preparation of dendralene-type chromophores with both TCBD and 1,2-bis(1,3-dithiol-2-ylidene)ethane units by the sequential [2+ +2] CA-RE reaction of TCNE and TTF with DAA-substituted butadiynes.…”
Section: Compoundmentioning
confidence: 99%
“…As ar esult, TCBD-TTF adduct 13 and dendralene 14 were prepared, and their multistage redox properties and extremelyl ow reduction potentials were revealed. [41] Similar to the reactiono f1 -ethynylazulenes, 1-azulenylbutadiynesw ere prepared from 1-ethynylazulene derivatives using Glaser-Hayc oupling by reactingt hem with TCNE under mild conditions to give the corresponding 1-AzTCBDs 11 and 12 bearinga ryl alkyne substituents. The alkyne moietyof11 reacted with TTF to give TCBD-TTF adduct 13 (Scheme 6).…”
Section: -Azulenyl Tcbds With Aryl Substituentsmentioning
confidence: 99%